NADPH Oxidase 5 and Melatonin: Involvement in Ram Sperm Capacitation - Miguel-Jiménez, Sara; Pina-Beltrán, Blanca; Gimeno-Martos, Silvia; Carvajal-Serna, Melissa; Casao, Adriana; Pérez-Pe, Rosaura (Frontiers in Cell and Developmental Biology, 2021)
Reactive oxygen species (ROS) play an essential role in mammalian sperm capacitation. NADPH oxidase 5 (NOX5) has been described as the main source of ROS production in some mammalian spermatozoa, such as human and equine. On the other hand, melatonin can decrease cellular ROS levels and regulates NOX activity in somatic cells. Therefore, the objectives of this work were 1) to identify NOX5 in ram spermatozoa and analyse its possible changes during in vitro capacitation and 2) to investigate the effect of melatonin on NOX5 expression and localization and on superoxide levels in capacitated ram spermatozoa. Protein bands associated with NOX5 were detected by Western blot analysis. Likewise, indirect immunofluorescence (IIF) revealed six different immunotypes for NOX5, which varied throughout in vitro capacitation. Superoxide (O2·-) , evaluated by DHE/Yo-Pro-1, rose after in vitro capacitation and in the presence of the calcium ionophore A23187, but decreased in the presence of the NOX inhibitor GKT136901. GKT also reduced the percentage of capacitated and acrosome-reacted spermatozoa that had increased during incubation in capacitating conditions. The presence of melatonin at micromolar concentration avoided the increment in O2·- and the changes in NOX5 immunotypes provoked by capacitation. In conclusion, NOX5 is present in ram spermatozoa and the changes in its distribution, associated with sperm capacitation, can be prevented by melatonin. To this extent, it could imply that melatonin exerts its antioxidant role, at least in part, by modulating NOX5 activity during ram sperm capacitation.